Mild encephalitis/encephalopathy with reversible splenial lesion (MERS) associated with Streptococcus pneumoniae Bacteraemia. Issue 4 (July 2017) - Avcu, Gulhadiye; Kilinc, Mehmet A.; Eraslan, Cenk; Karapinar, Bulent; Vardar, Fadil
Summary: Mild encephalopathy with a reversible splenial lesion (MERS) is a clinico-radiological syndrome that can be related to infectious and non-infectious conditions. Patients present with mild neurological symptoms, and magnetic resonance imaging typically demonstrate a reversible lesion with transiently reduced diffusion in the splenium of the corpus callosum. Here, we describe MERS in a 10-year-old boy who presented with fever and consciousness and who completely recovered within a few days. Streptococcus pneumoniae was the causative agent. Although viruses (especially influenza A and B) are the most common pathogen of MERS, for proper management, bacteria should be considered, as they may also lead to this condition.